Epigenetic Modifications in Cervical Cancer Progression: Diagnostics and Therapeutic Potential - Farooq Khawaja, Yusha Ibn Umar; Aziz, Muhammad; Iqbal , Naveed; Nadeem, Habibah; Maqbool, Sumrah; Saeed, Imran (Indus Journal of Bioscience Research, 2025)
We conducted this study to understand the size of the problem, how key epigenetic changes relate to clinical factors and their usefulness in predicting outcomes in cervical cancer patients. The study included 120 women who had cervical cancer and were being treated in hospital oncology and gynecology departments. DNA methylation, histone modification H3K27me3, miR-21 levels and lncRNA HOTAIR expression were all studied in this research using descriptive, chi-square and regression methods. A large number of these alterations were found in the patients studied, as DNA methylation was seen in 70.8%, histone modification in 65.0%, overexpression of miR-21 in 75.0% and elevated HOTAIR genes in the case of 60.0% of patients. Results from chi-square tests confirmed that each of these markers was significantly connected to how far the tumor advanced (p < 0.05). In addition, regression analysis identified these markers as reliable predictors of advanced tumor stages. The results are consistent with what other studies have said about epigenetics in cancer development and therapy resistance. It recommends that clinicians use epigenetic profiling to better follow patient disease progression and that future studies examine the modifications of these markers to improve personalized care for cervical cancer patients.